Sustainable quality culture in schools: a leadership perspective - Tataq Harjuna Piranggada; Muhammad Triyoso; Nur Kholis Usman; Miad Miad; Khairul Efendi; Aslamiah Aslamiah; Celia Cinantya (Universitas Pendidikan Indonesia, 2025)
A sustainable quality culture is an institutional prerequisite for responding to demands for educational accountability in Indonesia. However, its implementation faces challenges related to leadership, professional collaboration, and variations in socio-educational contexts. This study aims to analyze the role of principal leadership in strengthening the SPMI cycle, examine the mediating function of PLCs, and identify the influence of contextual factors on the sustainability of a quality culture in secondary schools. An integrative literature review method was employed, with searches conducted in Google Scholar, Garuda, and DOAJ, guided by thematic relevance, peer-reviewed publications from 2014-2025, and operational clarity of variables. The synthesis results indicate three main levers: consistent, learning-oriented instructional-transformational leadership, PLCs institutionalized as collaborative inquiry, and integrated SPMIs with data utilization based on continuous improvement cycles. The analysis found that PLCs act as mediators, translating leadership vision into changes in classroom practices, whereas socio-geographical contexts moderate the effectiveness of implementation. The sustainability of a quality culture requires systemic integration between instructional leadership, professional collaborative mechanisms, and adaptation to local characteristics. Therefore, a differential strategy in quality mentoring and a multi-level longitudinal research design are needed to strengthen theoretical validity. Abstrak Budaya mutu berkelanjutan menjadi prasyarat institusional dalam merespons tuntutan akuntabilitas pendidikan di Indonesia, namun implementasinya menghadapi tantangan kepemimpinan, kolaborasi profesional, dan variasi konteks sosial-edukatif. Penelitian ini bertujuan menganalisis peran kepemimpinan kepala sekolah dalam menguatkan siklus SPMI, menelaah fungsi mediasi PLC, serta mengidentifikasi pengaruh faktor kontekstual terhadap keberlanjutan budaya mutu di sekolah menengah. Metode literature review integratif digunakan dengan penelusuran melalui Google Scholar, Garuda, dan DOAJ menggunakan kriteria relevansi tematik, publikasi peer-reviewed tahun 2014-2025, serta kejelasan operasional variabel. Hasil sintesis menunjukkan tiga pengungkit utama: kepemimpinan instruksional-transformasional yang konsisten berorientasi pembelajaran, PLC yang terlembaga sebagai inkuiri kolaboratif, serta SPMI terintegrasi dengan pemanfaatan data berbasis siklus perbaikan berkelanjutan. Analisis menemukan bahwa PLC berperan sebagai mediator yang menerjemahkan visi kepemimpinan menjadi perubahan praktik kelas, sedangkan konteks sosial-geografis memoderasi efektivitas implementasi. Keberlanjutan budaya mutu memerlukan integrasi sistemik antara kepemimpinan pembelajaran, mekanisme kolaboratif profesional, dan adaptasi terhadap karakteristik lokal, sehingga diperlukan strategi diferensial dalam pendampingan mutu serta desain riset longitudinal multi-level untuk memperkuat validitas teoretis. Kata Kunci: budaya mutu; kepemimpinan kepala sekolah; perbaikan berkelanjutan; PLC